LC-MS-Q-TOF identification of xanthine oxidase inhibitory phytoconstituents from Averrhoa bilimbi leaves - Ahmed, Qamar Uddin; Alhassan, Alhassan Muhammad; Sarian, Murni Nazira (2018)
Averrhoa bilimbi (family: Oxalidaceae) leaves preparations are used in traditional medicine in Malaysia for treatment of several diseases including diabetes. The objective of this study was to investigate the xanthine oxidase (XO) inhibitory potential of A. bilimbi leaves and identification of its bioactive constituents through LC-MS-Q-TOF analysis. A. bilimbi leaves crude methanol extract was fractionated with hexane, chloroform and n-butanol. The fractions at different concentrations were subjected to XO inhibitory activity investigation. LC-MS-Q-TOF profiling of the most active fraction was carried out to identify the active compound. Molecular docking was used to investigate the potential inhibitory effect of the active compounds identified through LC-MS-Q-TOF analysis. Results for XO assay demonstrated for n-butanol fraction to display significant inhibitory activity (IC50: 64.84 ± 3.93 μg/mL). However, hexane and chloroform fractions did not show good inhibitory activity. (Z)-Resveratrol-3,4ʹ-β-glucoside and afzelechin-3-O-α-L-rhamnopyranoside were identified in n-butanol fraction through LC-MS-Q-TOF analysis as the possible metabolites responsible for XO inhibitory activity of the n-butanol fraction. Further scientific effort is, however, needed to obtain such bioactive compounds in pure form for complete pharmacological evaluations.